Energy-dispersive X-ray diffraction mapping on a benchtop X-ray fluorescence system - Lane, David W.; Nyombi, Antony; Shackel, J. (Blackwell Publishing Ltd, 2014)
A method for energy-dispersive X-ray diffraction mapping is presented, using a conventional low-power benchtop X-ray fluorescence spectrometer, the Seiko Instruments SEA6000VX. Hyper spectral X-ray maps with a 10µm step size were collected from polished metal surfaces, sectioned Bi, Pb and steel shot gun pellets. Candidate diffraction lines were identified by eliminating those that matched a characteristic line for an element and those predicted for escape peaks, sum peaks, and Rayleigh and Compton scattered primary X-rays. The maps showed that the crystallites in the Bi pellet were larger than those observed in the Pb and steel pellets. The application of benchtop spectrometers to energy-dispersive X-ray diffraction mapping is discussed, and the capability for lower atomic number and lower-symmetry materials is briefly explored using multi-crystalline Si and polycrystalline sucrose.